Determinant factors of the implementation of the balanced scorecard in Portugal : empirical evidence in public and private organizations - Quesado, Patricia Rodrigues (2014)
In this article we aim to identify and analyze a set of variables that can potentially influence the adoption of the Balanced Scorecard (BSC) in Portugal. Hypotheses were tested using data obtained from a questionnaire sent to 591 publicly-owned organizations (local governments, municipal corporations and hospitals) and 549 privately-owned organizations (large companies and small and medium enterprises) in Portugal, with an overall response rate of 31.3%. The results allow us to conclude that although the majority of respondents claimed to know the BSC, its use in Portugal is still limited and very recent, particularly in the public sector organizations. However, it should be noted that its use has increased in Portugal in recent years. Using as theoretical framework the contingency and institutional theories, we found that decentralization, vertical differentiation and the degree of higher education are associated with the implementation of the BSC